Getting to Know More about Tetanus - Faqih, Fauzan; Aritiah, M. Awalul Rizky; Solihatin, Illiyani; Afifah, Fiza; Faranajhia, Hagia; Wicaksono, Teguh Budi; Irmayanto, Tomi (Universitas Ibn Khaldun Bogor, 2025)
Tetanus is an acute disease that affects the central nervous system caused by tetanospasmin toxin produced by Clostridium tetani. Tetanus is a deadly disease in developing countries, killing approximately 500,000 people per year. This is due to lack of hygiene, easy contamination, poor wound care, lack of public awareness of the importance of hygiene and tetanus vaccination. In general, tetanus is characterized by rigidity, muscle spasm and autonomic disorders. Spasms almost always occur in the neck and jaw muscles causing jaw closure (trismus, lockjaw) and involve not only the extremity muscles, but also the trunk muscles. Tetanus is not transmitted from human to human and can be prevented through immunization. Clostridium tetani is quite widespread in nature and cannot be eradicated. To reduce the number of cases, tetanus treatment efforts focus on prevention using vaccination with active immunization or passive immunization and post-exposure care.